Complete Remission of Advanced Adrenocortical Cancer Following Mitotane Monotherapy: A Case Report and Literature Review of Predictive Markers - Tőke, Judit; Jakab, Zsuzsanna; Stark, Júlia; Huszty, Gergely; Reismann, Péter; Tóth, Miklós (Frontiers in Oncology, 2021)
Mitotane has been used for the treatment of adrenocortical cancer (ACC) for over 50 years. Despite its widespread use both in monotherapy and in combination with chemotherapeutics, our knowledge of its mechanism of action and therapeutic efficacy is scarce. The number of patients with advanced ACC who have achieved complete remission documented by detailed clinical data is below ten. We report a case of a 64-year-old woman with a non-functional ACC. Histological examination showed vascular invasion, Ki67 of 10% and a mitotic count of 3/10 high-power field. Immunohistochemistry revealed p53 positivity. Pathological TNM grade was reported as T2N0M0, ENSAT stage 2. Nine months after the initial diagnosis, re-staging CT revealed multiple peritoneal nodules, lymph node and kidney metastases confirmed by histologic examination. Mitotane monotherapy was started with a maintenance dose between 2.0 and 2.5 grams/day. Partial remission was established at six months. Subsequently, for another 12 months, each of the three-monthly CT scans confirmed complete remission. Nineteen months after the initiation of mitotane, an unexpected sudden death occurred. A detailed autopsy work-up, performed in the full awareness of oncological history, confirmed complete remission. The authors review the molecular biomarkers and clinical features reported as predictors of response to mitotane monotherapy.